PENGARUH PERBEDAAN SUHU TERHADAP POTENSI TABLET SIPROFLOKSASIN (EKSPERIMEN DENGAN BAKTERI Escherichia coli) - Rauhul Akbar Kurniawan; Yunan Jiwintarum; Liana Dwihartati (poltekkes kemenkes mataram, 2015)
Abstract: It has been conducted the determination of potency of Ciprofloxacin 500 tablets was storage in temperature 0°C, 10°C, 20°C, 30°C, 40°C for 20 hour. The aim of research is to find out the effect of different temperature for potency of Ciprofloxacin tablets. The method of determination applied is the measure diameter zone inhibition Escherichia coli in MHA. The result indicated that was negative interaction temperature storage for potency of Ciprofloxacin tablets.